The Second Galanin Receptor GalR2 Plays a Key Role in Neurite Outgrowth from Adult Sensory Neurons - Sally-Ann Mahoney; Richard Hosking; Sarah Farrant; Fiona E. Holmes; Arie S. Jacoby; John Shine; Tiina P. Iismaa; Malcolm K. Scott; Ralf Schmidt; David Wynick (2003)
Expression of the neuropeptide galanin is markedly upregulated within the adult dorsal root ganglion (DRG) after peripheral nerve injury. We demonstrated previously that the rate of peripheral nerve regeneration is reduced in galanin knock-out mice, with similar deficits observed in neurite outgrowth from cultured mutant DRG neurons. Here, we show that the addition of galanin peptide significantly enhanced neurite outgrowth from wild-type sensory neurons and fully rescued the observed deficits in mutant cultures. Furthermore, neurite outgrowth in wild-type cultures was reduced to levels observed in the mutants by the addition of the galanin antagonist M35 [galanin(1–13)bradykinin(2–9)]. Study of the first galanin receptor (GalR1) knock-out animals demonstrated no differences in neurite outgrowth compared with wild-type animals. Similarly, use of a GalR1-specific antagonist had no effect on neuritogenesis. In contrast, use of a GalR2-specific agonist had equipotent effects on neuritogenesis to galanin peptide, and inhibition of PKC reduced neurite outgrowth from wild-type sensory neurons to that observed in galanin knock-out cultures. These results demonstrate that adult sensory neurons are dependent, in part, on galanin for neurite extension and that this crucial physiological process is mediated by activation of the GalR2 receptor in a PKC-dependent manner.